Analyzing Grammar in Collocations Al Jazeera News Channel Texts and Its Influence on the Lexicon of Non-Arabic Speaking Learners/ تحليل المتلازمات اللفظية في نصوص قناة الجزيرة الإخبارية نحويًّا وأثرها في معجم المتعلّمين من غير الناطقين بالعربية - Abu Ghalyoun, Safaa Mohammad; Sapar, Ahmad Arifin; Seman, Haji Mohammad Bin (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This research seeks to address some of the most common verbal collocations that appear in the texts of Al Jazeera News Channel by studying linguistic and rhetorical analysis, exploring their composition and grammatical structure, and knowing the extent of their stability or transformation based on whether they are open or closed collocations, that is, knowing the extent to which they can accompany a limited or unlimited number of syllables. This study uses an analytical approach to the implications of news texts and their associations, describing them, and exploring their depth according to the grammatical basis of Al Jazeera News Channel. Data collection techniques use observation and interviews. There are idiomatic expressions that cannot be changed, which refer to sayings, proverbs, and verses of the Qur'an. They have complex rhetorical shifts, and it is impossible for a student who does not speak Arabic to understand the social and semantic meanings behind Arabic proverbs, sayings, stories, and history without the teacher's explanation or the presence of a dictionary that translates these stories into an intermediary language, which is not available in a large number of dictionaries that translate collocations. Because verbal collocations This is one of the most important requirements for understanding, learning, and practicing the language, because language lessons for each target group of students are related to knowledge of the semantic and social contexts behind various expressions and structures. A dictionary is needed to help understand and use collocations in the appropriate context, and explain the underlying cultural and metaphorical dimensions. Non-Arabic speakers find it difficult to explain or because of the complexity of their use and the inability of students to include the real context, so it must be taken into account when preparing various linguistic curricula and dictionaries.